2020
DOI: 10.3389/fpsyg.2020.566979
|View full text |Cite
|
Sign up to set email alerts
|

Team Member Work Role Performance: The Organizational Benefits From Performance-Based Horizontal Pay Dispersion and Workplace Benign Envy

Abstract: In the context of the current uncertain, complex, and interdependent work systems, teams have become organizations’ substantial working unit, which in turn challenges the traditional view of employee performance and ultimately results in the emergence of team member work role performance. Employee team-oriented work role behaviors with proficiency, adaptivity, and proactivity, which are integrated by the new construct, are so crucial to team effectiveness that many organizations keenly expect to achieve team m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…With this study, we argue that envy can have a significant impact on employees' job performance. In the literature, some of the studies on workplace envy and job performance relation were conducted within the frame of typological approach (De Clercq et al , 2018; Aydın-Küçük and Taştan, 2019; Lee and Duffy, 2019; Khan and Noor, 2020; Zhang et al , 2020) mostly indicating malicious envy related to poor performance whereas benign envy to improvement in performance. Although there also exists a recent interest in the situational approach, a limited number of studies are available in the literature (Eissa and Wyland, 2016; Lee et al , 2018; Treadway et al , 2019; Shousha, 2020; Tariq et al , 2019) that show how envying others and being envied can contribute to employees' job performance.…”
Section: Discussionmentioning
confidence: 99%
“…With this study, we argue that envy can have a significant impact on employees' job performance. In the literature, some of the studies on workplace envy and job performance relation were conducted within the frame of typological approach (De Clercq et al , 2018; Aydın-Küçük and Taştan, 2019; Lee and Duffy, 2019; Khan and Noor, 2020; Zhang et al , 2020) mostly indicating malicious envy related to poor performance whereas benign envy to improvement in performance. Although there also exists a recent interest in the situational approach, a limited number of studies are available in the literature (Eissa and Wyland, 2016; Lee et al , 2018; Treadway et al , 2019; Shousha, 2020; Tariq et al , 2019) that show how envying others and being envied can contribute to employees' job performance.…”
Section: Discussionmentioning
confidence: 99%
“…If they receive far less compensation than their fellows, in other words, the pay dispersion is large, this will lead to a feeling of inequity. The assessment of inequity can lead to a feeling of injustice and jealousy, which in turn may reduce team cohesion and decrease job satisfaction (Collischon and Eberl, 2020), and even lower firm performance (Patel et al, 2018;Zhang et al, 2020). Conversely, if managers get relatively equal compensation with others, these managers may generate a perception of fair treatment, which in turn improves team collaboration and firm performance.…”
Section: Social Comparison Theorymentioning
confidence: 99%
“…By establishing a general view of managerial pay dispersion research, studies on how managerial pay dispersion influences firm behavior such as firm performance (Jaskiewicz et al, 2017;Patel et al, 2018;Zhang et al, 2020), executive turnover (Ridge et al, 2017), and firm innovation (Yanadori and Cui, 2013;Amore and Failla, 2020) have been well researched. For firm performance, Jaskiewicz et al (2017) investigated this issue in family firms and found that pay dispersion among non-CEO top management team members could harm firm performance.…”
Section: Managerial Pay Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars up to now have explored HPD’s impacts on employee effort and engagement, 3–5 workforce productivity, 6 firm’s financial performance, 7 innovation performance, 8 trust, 9 affective commitment and turnover, 10 motivation, 11 and behavioral performance. 12 However, these studies have not reached unanimous conclusions. Taking the possible effect of HPD on employee effort for example, some researchers failed to find empirical evidence of positive or negative impact, 3 , 4 whereas, other researchers revealed that as HPD becomes larger, employee effort goes up and employee sabotage behavior turns stronger.…”
Section: Introductionmentioning
confidence: 96%